Knowledge and attitudes of hand, foot, and mouth disease infection among medical students and physicians at the University of Jeddah - Alshahrani, Najim Z.; Bukhari, Suzan M.; Bukhari, Lujain M.; Alghamdi, Lama S.; Aljohani, Shouq R.; Ghurab, Radwan A. (Frontiers in Tropical Diseases, 2024)
BackgroundRecent HFMD cases have surged in Saudi Arabia, highlighting a literature gap on healthcare professionals’ understanding and attitudes towards HFMD. This study evaluates and compares knowledge and attitudes among medical students and physicians at the University of Jeddah.MethodsAn analytical cross-sectional study design was employed to survey medical students and physicians at the University of Jeddah from 1 November 2023 to 1 January 2024. Participants were assessed using multiple-item scales to measure their knowledge (max score: 23) and attitudes (max score: 32) towards HFMD. Logistic regression analysis was utilized to explore the association between various independent factors and the outcomes of interest (knowledge and attitude levels).ResultsA total of 317 responses (260 medical students and 57 physicians) were analyzed. Among medical students, the analysis of knowledge scores revealed a mean score of 6.36, with a standard deviation (SD) of 5.68, a median score of 6, and an interquartile range (IQR) of 0-10. About 31.6% of the students demonstrated adequate knowledge of HFMD. Notably, students who had received education on HFMD showed significantly higher levels of knowledge compared to those who had not. For student attitudes towards HFMD, the mean score in the attitude group was 20.1, with a SD of 4.2, a median of 20, and an IQR of 16 to 23. Among physicians, the mean knowledge score for those with adequate knowledge was 14.3, with a SD of 4.3 and a median of 15, and an IQR of 12-18. Furthermore, 54.4% of the physicians showed good knowledge, with being single significantly associated with this higher level of knowledge. In terms of attitudes among physicians, the mean score for the positive attitude group was 19.8, with a SD of 5.92, and a median score of 20, with an IQR of 16 to 25.ConclusionThe study highlights a significant gap in knowledge and attitudes towards HFMD among healthcare professionals in Saudi Arabia.